Young People Who Meaningfully Improve Are More Likely to Mutually Agree to End Treatment - Edbrooke-Childs, Julian; Costa da Silva, Luís; Čuš, Anja; Liverpool, Shaun; Pinheiro Mota, Catarina; Pietrabissa, Giada; Bardsley, Thomas; Sales, Celia M. D.; Ulberg, Randi; Jacob, Jenna; Ferreira, Nuno (Frontiers in Psychology, 2021)
Objective: Symptom improvement is often examined as an indicator of a good outcome of accessing mental health services. However, there is little evidence of whether symptom improvement is associated with other indicators of a good outcome, such as a mutual agreement to end treatment. The aim of this study was to examine whether young people accessing mental health services who meaningfully improved were more likely to mutually agree to end treatment. Methods: Multilevel multinomial regression analysis controlling for age, gender, ethnicity, and referral source was conducted on N = 8,995 episodes of care [Female = 5,469, 61%; meanAge = 13.66 (SD = 2.87) years] using anonymised administrative data from young people's mental health services. Results: Compared to young people with no change in mental health difficulties, those showing positive meaningful changes in mental health difficulties were less likely to have case closure due to non-mutual agreement (Odds Ratio or OR = 0.58, 95% Confidence Interval or CI = 0.50–0.61). Similarly, they were less likely to transfer (OR = 0.61, 95% CI = 0.49–0.74) or end treatment for other reasons (OR = 0.59, 95% CI = 0.50–0.70) than by case closure due to mutual agreement. Conclusion: The findings suggest that young people accessing mental health services whose symptoms meaningfully improve are more likely to mutually agree to end treatment, adding to the evidence that symptom improvement may be appropriate to examine as an indicator of a good outcome of accessing mental health services.